Are maternal reflective functioning and attachment security associated with preadolescent mentalization? - Rosso, Anna Maria; Viterbori, Paola; Scopesi, Alda M. (Frontiers in Psychology, 2015)
This study investigated the impact of maternal reflective functioning (RF) and attachment security on children’s mentalization. The Adult Attachment Interview (AAI) was administered to mothers in a sample of 41 mother-preadolescent dyads. AAI transcripts were rated in terms of the Berkeley AAI System (Main & Goldwyn, 1998) and the Reflective Functioning Scale (RFS; Fonagy et al., 1998). Preadolescent mentalization was assessed using a semi-structured interview adapted from O’Connor & Hirsch (1999) and also by analyzing mental-state talk produced during an autobiographical interview. Relationships between maternal RF and children’s mentalization were analyzed, with consideration given to the different RFS markers and references to positive, negative, and mixed-ambivalent mental states. Children’s mentalization was positively correlated with the mother’s RF, particularly the mother’s ability to mentalize negative or mixed-ambivalent mental states. No significant differences in mentalization were observed between children of secure and insecure mothers.